The effect of waste polyethylene terephthalate fibers on the properties of self-compacting concrete using Iraqi local materials - Mahmoud, Zena; Al-Hadithi, Abdulkader; Aldosary, Muhannad (Iraqi Journal of Civil Engineering, 2023)
This study was conducted to examine the impact of plastic fibers (WPFs) in an effort to improve some of the features of self-compacting concrete (SCC) using Iraqi raw materials. Waste polyethylene terephthalate fibers (waste PET fibers) from used beverage bottles were added. Some tests were carried out to determine the effects of adding WPFs on the fresh properties of new concrete, while additional tests examined the mechanical properties of hardened concrete. Because of this, self-compacting concrete blends were created with a constant water-to-binder ratio of 0.32 and a binder content of 525 kg/m3. The designated plastic fiber percentages contents were 0%, 0.5%, 0.75%, and 1% of mix volume. Self-compacting concrete mixtures’ fresh characteristics were assessed for slump flow diameter, T50 slump flow concurrently, V-funnel flow concurrently, and L-box height ratio. The 28-day density, compressive strengths and flexural strength of self-compacting concretes were also measured. The use of plastic waste fibers had a slight effect on reducing the density of the produced concrete and a negative effect on the fresh properties. The compressive strengths were improved by using WPFs, with the maximum improvement equal to (11.065%) when compared to those made from the reference mix